PHYSICAL EDUCATION: THE CREATIVE PROCESS UNDER THE EDUCATIONAL LOOK OF THE ART MAKING ON BODY PRACTICES (Fiep Bulletin - online, 2013)
In this study the objective was to bring reflections about the artistic representations typical of the body practices of physical education, and from these notes look at how the creative process manifests itself, by pointing to the creativity aspects that can intervene constructively in the teachers' educational action. We conducted this research through literature review related to art, physical education and education, enriching it as in some moments, the theory is interlaced with the living experience in the educational field.
Keywords: creativity; physical education; body practices.